2,5-dimethylphenacyl esters: a photoremovable protecting group for phosphates and sulfonic acids - Klán, Petr; Pelliccioli, Anna Paola; Pospísil, Tomás; Wirz, Jakob (Photochemical & photobiological sciences, 2002)
2,5-Dimethylphenacyl phosphoric and sulfonic esters release the corresponding acids upon irradiation in nearly quantitative isolated yields, with quantum yields phi = 0.71 and 0.68 in methanol, 0.09 and 0.19 in benzene. In methanol solution the reactions proceed predominantly via the (Z)-photoenol, the lifetimes of which (20 and 25 micros) were determined by laser flash photolysis. The chromophore is proposed as an excellent photoremovable protecting group for use in organic synthesis and biochemistry.
Keywords: fotolýza; methanol; Photochemistry; kyseliny sulfonové; Organophosphates; Photolysis; fotochemie; Acetophenones; acetofenony; Benzene; lasery; benzen; Sulfonic Acids; organofosfáty; Kinetics; Quantum Theory; Esters; Isomerism; kvantová teorie; Methanol; isomerie; kinetika; Lasers; estery